2014
DOI: 10.1016/j.cej.2014.06.076
|View full text |Cite
|
Sign up to set email alerts
|

A novel dual-layer bicomponent electrospun nanofibrous membrane for desalination by direct contact membrane distillation

Abstract: In this study, a bicomponent nanofibrous composite membrane was fabricated by electrospinning and was tested for desalination by direct contact membrane distillation (DCMD). The nanofibrous membrane was composed of a dual-layered structure of poly(vinylidenefluoride-cohexafluoropropylene) (PH) nanofibers and polyacrylonitrile (PAN) microfibers. Morphological characterization showed slightly beaded cylindrical PH nanofibers with porosity of about 90%. The contact angles of PH and PAN nano/microfibers were 150 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(64 citation statements)
references
References 22 publications
0
64
0
Order By: Relevance
“…Contact angle, which was generally used to indicate hydrophobicity of membrane surface, was measured by Theta Lite 100 (Attension) (Biolin Scientific, Paramus, NJ, USA) with sessile drop method [24,26]. Then 5~8 µL of water droplet was placed onto the membrane surface for analysis.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Contact angle, which was generally used to indicate hydrophobicity of membrane surface, was measured by Theta Lite 100 (Attension) (Biolin Scientific, Paramus, NJ, USA) with sessile drop method [24,26]. Then 5~8 µL of water droplet was placed onto the membrane surface for analysis.…”
Section: Characterizationmentioning
confidence: 99%
“…After the neat membrane was heat-pressed, the band at 840 cm −1 representing the β phase increased from 53% to 63.6%, while the band in terms of the α phase did not appear after the heat-press treatment. The increase in the transmittance of β phase bands indicated the increase in the crystallinity of the membrane as the amorphous phase of the PVDF was converted into the β phase due to the mechanical deformation, caused by the pressure applied on the membranes during heat-pressing [25,26]. Vineet et al found that annealing PVDF …”
Section: Increased Crystallinity and Appearance Of α Phase After Annementioning
confidence: 99%
“…The driving force is the partial vapor pressure difference resulting from the thermal gradient between the hot feed and cool permeate streams [7,8]. Theoretically, it can reject 100% of the salts and non-volatile components at the feed.…”
Section: Introductionmentioning
confidence: 99%
“…The membrane porosity, defined as the volume of pores divided by the total volume of the membrane, was measured via a gravimetric method [7]. Membrane samples with equal sizes of 2 cm × 2 cm were immersed in ethanol (Scharlau).…”
Section: Porositymentioning
confidence: 99%
“…Generally, high osmotic flux and low structural parameter values were achieved for nanofiber membranes, making it a suitable method for fabrication of FO membranes. Nanofiber-supported TFC membranes applied for water-based separation processes have been the subject of various studies in the past [20][21][22][23][24][25][26][27]. While nanofiber electrospinning is a practical and noncostly method in membrane fabrication, it is still somehow limited by the electrospinning condition optimization, selection of specific materials suited for particular applications, nanofiber post-treatment [25], nanofiber strength and stability [28], membrane swelling [29], and poor adhesion of the selective polyamide layer from the nanofiber support [20].…”
Section: Introductionmentioning
confidence: 99%